Classification systems for platelet-rich plasma. (August 2019) - Rossi, L. A.; Murray, I. R.; Chu, C. R.; Muschler, G. F.; Rodeo, S. A.; Piuzzi, N. S.
Abstract : There is good scientific rationale to support the use of growth factors to promote musculoskeletal tissue regeneration. However, the clinical effectiveness of platelet-rich plasma (PRP) and other blood-derived products has yet to be proven. Characterization and reporting of PRP preparation protocols utilized in clinical trials for the treatment of musculoskeletal disease is highly inconsistent, and the majority of studies do not provide sufficient information to allow the protocols to be reproduced. Furthermore, the reporting of blood-derived products in orthopaedics is limited by the multiple PRP classification systems available, which makes comparison of results between studies challenging. Several attempts have been made to characterize and classify PRP; however, no consensus has been reached, and there is lack of a comprehensive and validated classification. In this annotation, we outline existing systems used to classify preparations of PRP, highlighting their advantages and limitations. There remains a need for standardized universal nomenclature to describe biological therapies, as well as a comprehensive and reproducible classification system for autologous blood-derived products. Cite this article: Bone Joint J 2019;101-B:891–896.